2012
DOI: 10.1128/jvi.00736-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Patterns of Intrahuman Dengue Virus Diversity Reveal Associations with Viral Phylogenetic Clade and Interhost Diversity

Abstract: Analogous to observations in RNA viruses such as human immunodeficiency virus, genetic variation associated with intrahost dengue virus (DENV) populations has been postulated to influence viral fitness and disease pathogenesis. Previous attempts to investigate intrahost genetic variation in DENV characterized only a few viral genes or a limited number of full-length genomes. We developed a whole-genome amplification approach coupled with deep sequencing to capture intrahost diversity across the entire coding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 77 publications
(105 reference statements)
6
79
1
Order By: Relevance
“…An alignment with tissue culture-adapted DENV2 NGC, DENV2 PLO46, and DENV2 E124/E128 envelope protein with 21 envelope proteins sequenced directly from the serum of patients showed that residues proposed to interact with heparan sulfate were conserved (22,24,25). This analysis suggested that low-and high-affinity heparan sulfate binding viruses exist in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alignment with tissue culture-adapted DENV2 NGC, DENV2 PLO46, and DENV2 E124/E128 envelope protein with 21 envelope proteins sequenced directly from the serum of patients showed that residues proposed to interact with heparan sulfate were conserved (22,24,25). This analysis suggested that low-and high-affinity heparan sulfate binding viruses exist in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Because low affinity to heparan sulfate increases in vivo pathogenesis of dengue and a number of other viruses (22), and because high-affinity interactions with heparan sulfate can evolve during tissue culture passaging, we aligned tissue culture-adapted DENV2 NGC, DENV2 PLO46, and DENV2 E124/E128 envelope protein with 21 envelope proteins previously sequenced directly from the serum of patients with secondary dengue fever, dengue hemorrhagic fever, and dengue septic shock 1 to 5 days postinfection (dpi) and analyzed residues previously proposed to interact with heparan sulfate (22,24,25). The resolving of the crystal structure of the dengue virus envelope, in addition to mutational studies, has identified multiple basic residues that may interact with heparan sulfate (22,25).…”
Section: Mosquito Saliva Enhances Dengue Virus Infectivity In Fibroblmentioning
confidence: 99%
“…ORF1, in contrast, contains housekeeping genes, which are less likely to be host specific. Cyclical host jumps seen in arboviruses, e.g., West Nile virus, are associated with purifying selection (33,34). The concept behind this is that only substitutions conferring a selection advantage in both hosts are preserved.…”
Section: Discussionmentioning
confidence: 99%
“…These replacements may begin with a cloud of closely related virus strains (i.e., intrahost viral diversity), generated in part by the error-prone RNA-dependent RNA polymerase of DENV (15,16). The intrahost diversity of viruses is typically described in chronic infections, such as those caused by HIV and hepatitis C virus (17)(18)(19), but has also been found in acute infections with DENV and other RNA viruses (20)(21)(22)(23). During arbovirus infections, such populations are subject to natural selection in both the mosquito and the human host.…”
mentioning
confidence: 99%